SPECKLE NOISE REDUCTION IN COMPUTED TOMOGRAPHY IMAGE USING WEINER GUIDED FILTER - L., SASI KUMAR; THAYALANAYAKI, (International Journal of Psychosocial Rehabilitation, 2020)
Presently, noise reduction is a significant job in the medical field. It is useful to conclude a sickness. The outcome picture quality is estimated by the PSNR, RMSE, and MSE. Speckle noise, gaussian noise, and salt and pepper noise are used in the CT, MRI, and ultrasound scans. In this paper, we executed one of the new filters called WG-filter for restorative picture denoising. The proposed filter is productive and performs well in expelling Gaussian noise and speckle noise, and its presentation is poor for salt and pepper noise. Weiner guided filter mainly focuses on speckle noise and gaussian noise removal, especially in the CT scan images.